Ovulation rates in a stair-step protocol with Letrozole vs clomiphene citrate in patients with polycystic ovarian syndrome - S. Thomas; I. Woo; J. Ho; T. Jones; R. Paulson; K. Chung; K. Bendikson (BMC, 2019)
Abstract Purpose To compare ovulation rates between Letrozole and Clomiphene Citrate (CC) using a stair-step protocol to achieve ovulation induction in women with Polycystic Ovarian Syndrome (PCOS). Methods This is a retrospective cohort of predominantly Hispanic PCOS women of reproductive age who completed ovulation induction (OI) comparing women who underwent Letrozole stair-step protocol to those who underwent OI with CC stair-step. All women had a diagnosis of PCOS based on the 2003 Rotterdam criteria. For both protocols, sequentially higher doses of Letrozole or CC were given 7 days after the last dose if no dominant follicles were seen on ultrasonography. The primary outcome was ovulation rate (determined by presence of a dominant follicle) between the two treatment groups. Secondary outcomes included time to ovulation, clinical pregnancy rates and side effects. Results 49 PCOS patients completed a Letrozole stair-step cycle and 43 completed a CC stair-step cycle for OI. Overall, demographics were comparable between both groups. Ovulation rates with the Letrozole stair-step protocol were equivalent to CC stair-step protocol (96% vs 88%, p = 0.17). Although the mean time (days) to ovulation was shorter in the Letrozole group (19.5 vs 23.1, p = 0.027), the pregnancy rates were similar for both groups. Conclusions This is the first study to date that has compared the efficacy of the stair-step protocol in PCOS patients using Letrozole and CC. Both Letrozole and CC can be prescribed in a stair-step fashion. Letrozole stair-step was as efficacious as CC stair-step; patients achieved comparable rates of ovulation and clinical pregnancy. Time to ovulation was shorter in the Letrozole protocol.